A development of conceptual framework for sustainable mangrove forest programs participations in Malaysia - Wan Marican, Nurshahirah; Mohd Nawi, Nolila; Kamarulzaman, Nitty Hirawaty; Samdin, Zaiton (Institut Kajian Dasar Pertanian dan Makanan, Universiti Putra Malaysia, 2015)
Mangrove is a valuable plant. Its benefits cover from our daily use as a timber and charcoal, as well as in balancing the ecosystem since mangrove provides a breeding ground for flora and fauna. Southeast Asian region has been known as the world largest area for a mangrove forest. However, more than 20% the mangrove area s have s been degraded in the past two decades. Thus, the sustainability of the mangrove forest needs to be studied including such as programs on sustainable mangrove forest uses. Recent literature on sustainable mangrove forest programs show that there are several elements such as awareness, knowledge, attitude, and social influence that contribute to public intention to participate. These elements can be related with the development of a conceptual framework for the study. A framework is crucial in a study as it is used an outline for the research; it will assist in directing the flow of a study and in helping to achieve the objective. The theory of planned behavior (TPB) is widely used in research to explain and predict human behavior based on attitude, subjective norms, perceived behavior control and behavioral intention. TPB is being used as a based model of this study with other elements being adapted from previous studies. Previous studies show that awareness, attitude, socio-demographic factor, perceived behavior control, and subjective norm are elements that will impact public intention to participate in sustainable mangrove forest programs. These elements will be used in developing the conceptual framework of this study in order to understand and define why they are relevant to be used. Hence, the main objective of this paper is to develop a conceptual framework that can be used to measure public intention to participate in the sustainable mangrove forest programs in Malaysia.